The silver chair - Lewis, C. S. (Clive Staples) 1898-1963 (Macmillan, 1953)
Two English children undergo hair-raising adventures as they go on a search and rescue mission for the missing Prince Rilian, who is held captive in the underground kingdom of the Emerald Witch.